Pelatihan Kompetensi Mengetik Cepat dengan Penerapan Typing Master di SMK Negeri 9 Bandar Lampung - Suripto Suripto; Eri Maryani; Putri Irmala Sari; Supriyanto Supriyanto (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Fast 10 Finger Typing is a blind typing method which means we only value what we are going to type and use our instincts without looking at the keyboard. This technique is used to optimize the function of the fingers and the eyes do not get tired easily because they focus on the typed writing. This technique has an arrangement of placing the fingers so that all fingers can function in typing. This 10 finger typing exercise will apply a fast typing method, namely by using the typing master method.This service activity aims to help users to be able to type quickly. The typing master method, also known as training, is a good way of teaching to instill certain habits. Also as a means to maintain good habits. In addition, this method is also good for obtaining dexterity, accuracy, opportunity and skills. The typing master method in the current era is very helpful in the typing skills needed by a secretary or administrative employee, in the business or office world, such as hospitality, travel, limited liability companies. , Firms and government agencies such as education.Fast typing competition training with the application of typing master for students of SMKN 9 Bandar Lampung, to be able to further improve their mastery and skills in fast typing.